2007
DOI: 10.1080/10426910601063386
|View full text |Cite
|
Sign up to set email alerts
|

Chemically and Thermally Treated Vegetable Fibers for Reinforcement of Cement-Based Composites

Abstract: International audienceThis paper presents the effects of chemical and thermal treatments on the strength of vegetable fibers that were being considered as reinforcements in cementitious matrix composites for affordable housing. These include vegetable fibers extracted from banana trunks and sugar cane residues. The results suggested that pyrolysis increased the fiber strength, at least by a factor three. Acid attack generally degraded the strengths, while alkali attack had only a limited effect. Pyrolyzed bana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 47 publications
2
38
0
1
Order By: Relevance
“…0 37·87 37·87 32·77 32·27 43·52 43·52 30·17 30·17 2 54·71 52·64 46·09 43·54 61·78 59·02 44·73 43·65 4 64·29 55·93 51·27 54·40 73·67 66·87 55·13 52·83 6 78·61 70·37 76·16 60·61 79·81 73·23 65·29 65·88 Ternary and CLA identify the matrix; B for untreated fibers and P for pyrolyzed fibers Adding fibers leads to reduced bending strengths of the composites for both matrices, whatever the age and the fiber pretreatment. This behavior has already been observed by Arsène et al 11 in the case of composites prepared with chemically treated (sulfuric acid 5% by mass) bagasse fibers, and they attributed this to the lack of adhesion between the fibers and the matrix and a different void entrapment due to the fiber treatment. In addition, the composite pads were pressed at 0·5 MPa, which is six to ten times lower than the pressure proposed by Savastano et al, 13 leading to the presence of more porosity.…”
Section: Specific Heatsupporting
confidence: 50%
See 1 more Smart Citation
“…0 37·87 37·87 32·77 32·27 43·52 43·52 30·17 30·17 2 54·71 52·64 46·09 43·54 61·78 59·02 44·73 43·65 4 64·29 55·93 51·27 54·40 73·67 66·87 55·13 52·83 6 78·61 70·37 76·16 60·61 79·81 73·23 65·29 65·88 Ternary and CLA identify the matrix; B for untreated fibers and P for pyrolyzed fibers Adding fibers leads to reduced bending strengths of the composites for both matrices, whatever the age and the fiber pretreatment. This behavior has already been observed by Arsène et al 11 in the case of composites prepared with chemically treated (sulfuric acid 5% by mass) bagasse fibers, and they attributed this to the lack of adhesion between the fibers and the matrix and a different void entrapment due to the fiber treatment. In addition, the composite pads were pressed at 0·5 MPa, which is six to ten times lower than the pressure proposed by Savastano et al, 13 leading to the presence of more porosity.…”
Section: Specific Heatsupporting
confidence: 50%
“…In CLA composites, the optimal amounts of fibers leading to high strengths are around 2-4% by mass for raw fibers, while for pyrolyzed fibers, the optimal content is noted for 2 wt%. Arsène 11 have already observed this optimal content for pyrolyzed fibers in a commercial matrix. In the ternary matrix, the decrease in the bending strength is observed for increasing amounts of pyrolyzed fibers; this maybe due to low fiber/matrix adhesion; in this case, crack propagation is faster.…”
Section: Specific Heatmentioning
confidence: 99%
“…La cás-cara está formada aproximadamente por 95% de materia orgánica y 5% de minerales presentes en las cenizas (generalmente Si, Ca, Mg, K, Al, P, S, Cl). La bibliografía muestra que la composición química de la cáscara de maní está formada principalmente por celulosa, lignina y hemicelulosa (8). Contiene además otros polisacáridos, lípidos, proteínas, minerales, azúcares libres, resinas (Tabla 6).…”
Section: Agregado: Cáscaras De Maníunclassified
“…Fengel and Wegener (1983) have reported that the different alkali solution (KOH, Ca(OH) 2 , NaOH) and its concentration have an effect on the degree of swelling and in the transformation into cellulose-II which affects the quality of the fibers. Also, author researchers reported that treatment with Ca(OH) 2 decreased the tenacity of fibers more than treatment with NaOH (Arsene et al, 2007). The treatment with sodium hydroxide changes the topography of the surface of the fibers, removing the components of the cuticle, the pectin, and partially the lignin and the hemicelluloses (Mwaikambo et al, 1999).…”
Section: Effect Of the Concentration Of Naohmentioning
confidence: 99%